PLASTIC WASTE DIVERSIFICATION FOR ENVIRONMENTAL SUSTAINABILITY: EMPOWERING COASTAL COMMUNITIES - Waldan, Raziki; Wardi, Suhra (GERVASI: Jurnal Pengabdian kepada Masyarakat, 2025)
The plastic waste problem in Sungai Kunyit Village, Mempawah Regency, has to significant environmental pollution, particularly in coastal and riverine areas. This community service program aimed to empower residents by diversifying plastic waste into economically valuable products, supporting environmental conservation, and enhancing the community's economic well-being. The method employed was Participatory Action Research (PAR), which actively involved the community at every stage of the program, from problem identification and plastic waste processing training to the marketing of recycled products. The program's results indicated that more than 80% of participants gained an increased understanding of the negative impacts of plastic waste and demonstrated behavioral changes in their household waste management. In addition, the community began developing community-based businesses by utilizing digital platforms to market recycled products such as shopping bags and flower pots. This program not only significantly improved environmental awareness but also created positive economic impacts that support the sustainability of coastal community livelihoods.